The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.1016/j.omtm.2020.05.026
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme Replacement Therapy Can Reverse Pathogenic Cascade in Pompe Disease

Abstract: Pompe disease, a deficiency of glycogen-degrading lysosomal acid alpha-glucosidase (GAA), is a disabling multisystemic illness that invariably affects skeletal muscle in all patients. The patients still carry a heavy burden of the disease, despite the currently available enzyme replacement therapy. We have previously shown that progressive entrapment of glycogen in the lysosome in muscle sets in motion a whole series of “extra-lysosomal” events including defective autophagy and disruption of a variety of signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(54 citation statements)
references
References 76 publications
(108 reference statements)
1
53
0
Order By: Relevance
“…The entrapment of lysosomal glycogen results in muscle damage by a number of pathogenic mechanisms, such as defective autophagy, calcium homeostasis, oxidative stress, and mitochondrial abnormalities [2]. Recently, metabolic abnormalities and energy deficits have also been shown to contribute to this pathogenic cascade [3]. The severity of clinical manifestations, tissue impairment and age of onset correlate with the residual enzymatic activity and can be classified into two forms: the Infantile Onset Pompe Disease (IOPD) or classical form has no or very low enzymatic activity levels, leading to severe general muscular weakness with floppy infant syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…The entrapment of lysosomal glycogen results in muscle damage by a number of pathogenic mechanisms, such as defective autophagy, calcium homeostasis, oxidative stress, and mitochondrial abnormalities [2]. Recently, metabolic abnormalities and energy deficits have also been shown to contribute to this pathogenic cascade [3]. The severity of clinical manifestations, tissue impairment and age of onset correlate with the residual enzymatic activity and can be classified into two forms: the Infantile Onset Pompe Disease (IOPD) or classical form has no or very low enzymatic activity levels, leading to severe general muscular weakness with floppy infant syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, the mechanism of impaired autophagosomal-lysosomal fusion, which can be directly observed by time-lapse microscopy of live fibers co-stained with LC3/LAMP1 [67], is not fully understood. Our recent finding of increased levels of galectin 3, a sensitive marker of endosomal/lysosomal damage, in KO muscle offers a possible explanation for the defective fusion [66].…”
Section: Beyond the Lysosome: Pathogenic Cascade And Muscle Regenerationmentioning
confidence: 90%
“…In a large preclinical study in KO mice, AT-GAA was shown to significantly outperform alglucosidase alfa in all measured outcomes: GAA uptake and activity, muscle strength, reduction in lysosomal size and glycogen levels, and mitigation of autophagic defect [92]. Furthermore, long-term treatment of KO with AT-GAA completely reversed muscle lysosomal glycogen accumulation, eliminated autophagic buildup in >80% of muscle fibers, and to a large degree restored AMPK/mTORC1 signaling, muscle proteostasis, and metabolic abnormalities [66]. This outcome is in striking contrast with the limited effect of a long-term treatment of KO mice with alglucosidase alfa at a similar dose of 20 mg/kg [22].…”
Section: Next-generation Ertmentioning
confidence: 91%
See 2 more Smart Citations